(untitled) (Anclajes, 2012)
Pedro Páramo (1955), by Juan Rulfo, and Los Sangurimas (1934), by José De la Cuadra, unusually rephrase topics and formal elements of the Latin-American regionalism. The presence of the complexity about some items that are related with orality, the passage and the creation of a mythic atmosphere with characters and with an own history in Los Sangurimas allows to relate De la Cuadra’s pursue with the narrative procedures and the aesthetic interest in Rulfo’s novel. In view of the their common challenge of representing a traditional community in the course of modernization, each work tries out a particular resolution which allows to read different inflections to the regionalist representation modes. This connection makes a double critic procedure possible: the updating of Pedro Páramo reading by framing it in a large process of preceding aesthetic searches and the revision of Los Sangurimas in Latin-American literature history.